Project Performance indicator: Net Present Value (NPV) or Economic Value Added (EVA) - Andía Valencia, Walter (2011)
This article provides an analysis of the profitability of investment projects and the usual indicators for determining such return, focusing on the study of Economic Value Added and Net Present Value, used tools in the field of finance, this will analyze concepts, interpretations and applications.